2015
DOI: 10.1186/s12885-015-1925-2
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing of tyrosine kinase inhibitor-resistant non-small-cell lung cancers in patients harboring epidermal growth factor-activating mutations

Abstract: BackgroundThe aim of this study was to detect the epidermal growth factor receptor (EGFR)-activating mutations and other oncogene alterations in patients with non-small-cell lung cancers (NSCLC) who experienced a treatment failure in response to EGFR-tyrosine kinase inhibitors (TKIs) with a next generation sequencer.MethodsFifteen patients with advanced NSCLC previously treated with EGFR-TKIs were examined between August 2005 and October 2014. For each case, new biopsies were performed, followed by DNA sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 49 publications
(41 reference statements)
0
28
0
1
Order By: Relevance
“…Another study reported a frequency of 38/123 patients (30.9%) with mutation in KDR gene in Malignant Pleural Mesothelioma [9]. It is noteworthy to mention here that, a study on non-small cell lung cancer reported high Q472H type of KDR mutation number in 33.3% patients [10] and in another study, it has been suggested to play a role of proto-oncogene in Lung Adeno-carcinoma [11]. Therefore, a high frequency (19.6%) of KDR mutation among the patients in our study may also indicate its role in developing cancer.…”
Section: Discussionmentioning
confidence: 94%
“…Another study reported a frequency of 38/123 patients (30.9%) with mutation in KDR gene in Malignant Pleural Mesothelioma [9]. It is noteworthy to mention here that, a study on non-small cell lung cancer reported high Q472H type of KDR mutation number in 33.3% patients [10] and in another study, it has been suggested to play a role of proto-oncogene in Lung Adeno-carcinoma [11]. Therefore, a high frequency (19.6%) of KDR mutation among the patients in our study may also indicate its role in developing cancer.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to EGFR T790M, NGS revealed several other acquired resistance mutations, including mutations in TP53, KDR, and KIT [103], and compound EGFR mutations (i.e. more than one mutation in the EGFR tyrosine kinase domain) [104].…”
Section: Genetic Analysismentioning
confidence: 99%
“…While the germline mutations are often overlooked by previously published clinical sequencing studies [19], we analyzed our cohort for germline mutations with potential clinical implications. For example, KIT p.M541L mutation detected in 146 (16%, 146/932) tumors and KDR p.Q472H mutation in 5 (0.5%, 5/932) tumors are associated with resistance to EGFR inhibitors in NSCLCs [37]. The KDR p.Q472H germline mutation also confers increased sensitivity to antiangiogenesis treatment in melanomas [38].…”
Section: Germline Mutations With Clinical Implicationsmentioning
confidence: 99%